PENGARUH SIKAP, MOTIVASI, DAN KETERAMPILAN BIDAN TERHADAP PENERAPAN METODE ASUHAN PERSALINAN NORMAL (APN) DI PRAKTIK MANDIRI BIDAN KOTA TERNATE: THE INFLUENCE OF MIDWIVES ATTITUDES, MOTIVATIONS, AND SKILLS ON THE APPLICATION OF THE NORMAL DELIVERY CARE METHOD (APN) IN THE INDEPENDENT PRACTICE MIDWIFE OF TERNATE CITY - Sulastri, Eni; Linda, Sri (Jurnal Medikes (Media Informasi Kesehatan), 2020)
Normal delivery care is carried out with the aim of maintaining survival and providing a high degree of health for the mother and her baby, through integrated and complete efforts but with minimal interventions so that the principle of safety and service quality can be maintained at the desired level (optimal). Safe labor is really needed because labor is a normal process and a healthy event. However, the potential for life-threatening complications will always be there, so the midwife must closely observe the mother and baby throughout the birth. In addition, all birth attendants must have the knowledge, skills, and tools to provide safe and clean assistance, and pay attention to the surrounding environment. Midwives can also be one of the factors that play a role in the normal delivery service process, the competence possessed by midwives in assisting childbirth is not necessarily the same as implementing a normal delivery care service consisting of 60 steps. the service. This study aims to determine the effect of midwives' attitudes, motivations and skills on the application of the normal delivery care method (APN). This study is a quasi-experimental using a one group design pattern with measurements of pre test and post test (one group pretest posttest design).